PENGARUH AKTIVITAS PEMASARAN DAN KINERJA PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Sari, Oktora Yogi; Yuniarti, Rita (Fakultas Ekonomi Universitas Garut, 2024)
Marketing is becoming a function that cannot be separated from the company's strategic implementation. For this reason, marketing activities should be integrated with all strategic functions of the company. This research aims to examine the impact of marketing activities and firm performance on company value in 32 manufacturing sector companies listed on the Indonesia Stock Exchange for the period of 2019 - 2022. Companies that focus on customer acquisition and retention through targeted marketing are more likely to achieve steady revenue, which contributes to greater financial stability and increased market value. On the other hand, factors like Debt-to-Equity Ratio (DER), Return on Assets (ROA), and Credit Ratios do not directly affect a company’s value.